Evaluation of Advanced Field Epidemiology Training Programs in the Eastern Mediterranean Region: A Multi-Country Study - Al Nsour, Mohannad; Khader, Yousef; Bashier, Haitham; Alsoukhni, Majd (Frontiers in Public Health, 2021)
Field Epidemiology Training Programs (FETPs) are competency-based training programs aiming to strengthen epidemiologic capacity of public health workforce. This study aimed to evaluate the impact of the Advanced FETPs in the Eastern Mediterranean Region (EMR) and ascertain whether the expected objectives of the programs are met. A descriptive study was conducted based on the Kirkpatrick’s model for evaluating training programs. Data were collected from FETP graduates and FETP technical advisers on the practices of FETP graduates, their engagement in key areas of field epidemiology, and their perceived skills and capacity to perform such activities. A total of 166 FETP graduates responded to the online survey. Almost two thirds of FETP graduates reported that they are often engaged in managing public health surveillance system (n=119, 71.7%), analyzing the surveillance data (n=116, 69.9%), training public health professionals (n=113, 68.1%), outbreaks investigations and response (n=109, 65.7%), and managing staff and resources (n=106, 63.9%). However, only 28.3% reported that they are often engaged in writing scientific research articles. More than two thirds of graduates reported that the FETP helped them to perform most of the field epidemiology activities and rated their skills as good. In conclusion, the FETP graduates in the EMR were well engaged in many field epidemiology activities including managing public health surveillance systems, surveillance data analysis, training public health professionals, and outbreaks investigations and response. Therefore, the FETPs should continue supporting the graduates to work toward strengthening surveillance systems and outbreak investigation and to participate in regional and global efforts as part of Global Health Security.